Authentication of medical images using passive approach. Issue 13 (11th October 2019) - Prakash, Choudhary Shyam; Om, Hari; Maheshkar, Sushila
Abstract : Telemedicine is getting a lot of popularity. It is because of the way that the medical images are sent over the Internet to share the restorative state of a patient, making the analysis simple for the medical staff. There is, however, a good possibility that the contents of a medical image may be altered due to the openness of the Internet. The watermarking techniques are utilised to keep the integrity of medical images intact. These techniques, however, need some additional information (watermark) to be embedded into the medical images, which may deteriorate their visual quality, leading to false diagnosis. In this study, a non‐intrusive procedure for verification of the medical images is proposed in which the polar cosine transform is used for feature extraction and the PatchMatch algorithm to locate the forged regions. Experimentally, the authors demonstrate that the proposed technique is robust against the noise, blurring, scaling, rotation and JPEG compression.